Perversion of the language in discourses of violence against women: Aproximación a las noticias de Oscar Pistorius - Bustinduy-Fernández, Sara (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This is a case study on a selection of five press articles about Oscar Pistorius murder trial of Reeva Steenkam. It is based on the author´s doctoral thesis from 2021 entitled “Análisis lingüístico de artículos de prensa en inglés y español sobre violencia contra la mujer: el caso de Reeva Steenkamp”. It will be argued that there are issues that deviate the discourse meaning with a perverse twist.